Influence of Chemical Refining Processes on the Total Phenolics and Antioxidant Activity of Sunflower Oil - Jhaumeer Laulloo, S; Gupta Bhowon, M; Hoolash, A (International Journal of Nutrition, 2015)
The raw sunflower oil (SFO) has an undesirable flavour and odour. Therefore, to make it suitable for human consumption, the oil has to undergo a number of refining processes such as degumming, neutralization, bleaching and deodorization. During these refining processes, some of the phytochemicals present in SFO is lost. The aim of this study is to evaluate the loss in total phenolic, flavonoid and non-flavonoid contents and the antioxidant properties of the oil at the different chemical refining stages. The crude SFO oil has the highest total phenolic, flavonoid and non-flavonoid contents. The amount of phenolic compounds decreases as the oil undergoes different chemical refining processes. Results of this study indicated that the highest percentage loss of the phenolic compounds occurred during the deodorizing step.The statistical loss of the deodorized oil was 41.7, 63.9 and 27.6 % for total phenolic, flavonoid and non-flavonoid contents respectively. The free scavenging activity of sunflower oil was determined using DPPH and ABTS assays. The percentage scavenging activity ranged from 55.64 to 35.87 % for the DPPH assay while for ABTS assay the activity ranged from 59.46 to 31.43 % in a 50 mg/ml of SFO sample. This showed a decrease in antioxidant activity from crude to DNW to bleached and deodorized oil. The crude oil having the highest phenolic contents showed the highest antioxidant activity in both DPPH and ABTS assays.
Keywords: Sunflower oil; antioxidant; phenols; flavonoid; non-flavonoid